An Updated Checklist of Avifauna found in and around Chilika Lake, Odisha, India - Gangaiamaran, Pichaimuthu; Sathiyaselvam, Ponnusamy; Balachandran, Sivananinthaperumal; Khan, Khursid A. (Indian Forester, 2020)
Chilika lake is one among the 467 important bird area (IBA) sites in India. The present study addresses the updated checklist ofavifauna of Chilika Lake, which is world's second largest brackish water Lake. Surveys were conducted during October 2006 and December 2016.The birds were recorded during the total count by boat, walking along the shore, block count, bird ringing, banding and satellite telemetry techniques. A total of 222 species ofavifauna of 62 orders and 20 families were recorded in and around study area. Nine (9) new bird species (River Lapwing Vanellus duvaucelli, Glossy Ibis Plegadis facinellus, Indian Thick-knee Burhinus indicus, Alexandrine Parakeet Pstittacula eupatria, Chestnut-headed Beeeater Merops leschenaultia, Wire-tailed Swallow Hirundo smithii, Whiterumped Munia Lonchura striata, Scaly-breasted Munia Lonchura punctulata and Black-hooded Oriole Oriolus xanthornus) were recorded first time in the study area. Out of total documented species, most of them were Least concern (201) followed by Near Threatened (17), Vulnerable (2) and Endangered (2) category of the International Union of Conservation of Endangered Fauna and Flora. The endangered species recorded from the study area were Pallas's fish eagle (Haliaeetus leucoryphus) and Great knot (Calidris tenuirostris). Prawn gharries, poaching, poisoning, illegal fishing, over fishing (operate zero size mesh net), habitat degradation and otheranthropogenic activities are the major threat to the conservation of avifauna in and around Chilika lake.